2005
DOI: 10.1590/s0100-40422005000500031
|View full text |Cite
|
Sign up to set email alerts
|

Los electrodos de pasta de carbono en el estudio electroquímico de minerales metálicos

Abstract: Recebido em 29/6/04; aceito em 8/11/04; publicado na web em 28/2/05 THE ROLE OF THE CARBON PASTE ELECTRODES IN THE ELECTROCHEMICAL STUDY OF METALLIC MINERALS. This paper shows the applicability of the carbon paste electrode-mineral (CPE-mineral) to study the dissolution mechanisms of minerals in powder form and in flotation concentrates. A potentiodynamic strategy to find the dissolution mechanism of galena (PbS) is presented. In this way, minerals less studied such as orpiment (As 2 S 3 ) and realgar (As 2 S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
5
0
4
Order By: Relevance
“…In recent years, there have been attempts to identify the processes involved in the formation of the above products by means of highly reproducible electrochemical surface characterization, using carbon paste electrodes and cyclic voltammetry [12][13][14][15][16][17]. However, many inconsistencies exist in the literature regarding the potential region in which voltammetric peaks related to passive behavior and the existence of covellite appear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been attempts to identify the processes involved in the formation of the above products by means of highly reproducible electrochemical surface characterization, using carbon paste electrodes and cyclic voltammetry [12][13][14][15][16][17]. However, many inconsistencies exist in the literature regarding the potential region in which voltammetric peaks related to passive behavior and the existence of covellite appear.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows a typical electrochemical response of pure arsenopyrite mineral without pretreatment, the sweep potential was initiated from the open circuit potential (OCP) in the anodic direction, with a sweep rate of 20 mV/s. Diverse voltammetric studies reported in the literature found that electro-oxidation of arsenopyrite in acidic medium takes place in two stages (Nava and González, 2007;Cruz et al, 2005;Lázaro et al, 1997). Initially, arsenopyrite is oxidized to realgar (As 2 S 2 ) and Fe (II) (A); after these species are interfacially formed, the second stage of the process begins (B): Fe (II) is oxidized to Fe (III).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies found that H 2 S was produced (Cama et al, 2005;Nava and Gonzalez, 2005). This would have oxidized immediately, leading to the production of hydrosulphuric acid and ultimately, sulphate.…”
Section: New Marine Deposition Theorymentioning
confidence: 99%